LDF's Repeat Performance Kerala's Local Body Elections - M R Biju (Economic and Political Weekly October 14-21, 1995, 1995)
In spite of its pro-backward class stance on the issue of reservations the UDF failed to win majority of local bodies due to infighting and emergence of divisions within the state's Muslim constituency.